The Influence of Trip Purpose on the Mode Choice Between High-Speed Train and Airplane: Leisure Vs. Non-Leisure Trip - Upahita, Dwi Phalita; Salsabila, Maharani Almira; Lestari, Meiyanne; Sucipto, Sucipto; Utomo, Djoko Prijo (RSF Conference Series: Engineering and Technology, 2022)
Jakarta – Surabaya Corridor plays an important role in connecting two major metropolitan cities in Java Island on each end and other cities in between the corridors. The corridor is currently served by highway, conventional rail network, and air transport mode. However, due to high trip demand, this corridor almost reaches its capacity. Developing a high-speed train network between Jakarta – Surabaya is one of the priority programs stated in the National Railway Masterplan (RIPNAS). The Jakarta – Surabaya high-speed train will be a competitor to the existing air transportation services, as both modes have competitive travel time and pricing. Previous studies have shown that operation HSR could have an adverse effect on the demand for airplane passengers. Passenger mode choice can be influenced by several factors, including the trip’s purpose. This study aims to understand the differences between leisure and non-leisure trip maker in choosing their mode. Specifically, this study focuses on the competition between a high-speed train and existing air transport service on Jakarta – Surabaya Corridor. A stated preference survey was used to collect data on passenger mode choice. The logit binomial model was used to model the mode choice, with time and cost differences as the quantitative independent variables and trip purpose as the qualitative variable. This study used a dummy variable to represent the different trip purposes, leisure and non-leisure. The result found that the odds ratio is 0.646, which indicated that passengers on leisure trips are less likely to move to HST from the airplane. This result is useful for the planner as it can indicate the potential passenger demographic and come up with services that suit their needs.